2008
DOI: 10.1124/jpet.108.138107
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of the Metabotropic Glutamate Receptor 1 Antagonist Compared with Those of the Metabotropic Glutamate Receptor 5 Antagonist and Metabotropic Glutamate Receptor 2/3 Agonist in Rodents: Detailed Investigations with a Selective Allosteric Metabotropic Glutamate Receptor 1 Antagonist, FTIDC [4-[1-(2-Fluoropyridine-3-yl)-5-methyl-1H-1,2,3-triazol-4-yl]-N-isopropyl-N-methyl-3,6-dihydropyridine-1(2H)-carboxamide]

Abstract: The functional roles of metabotropic glutamate receptor (mGluR) 1 in integrative brain functions were investigated using a potent and selective mGluR1 allosteric antagonist, FTIDC [4-[1-(2-fluoropyridine-3-yl)-5-methyl-1H-1,2,3-triazol-4-yl]-N-isopropyl-N-methyl-3,6-dihydropyridine-1(2H)-carboxamide], in comparison with the mGluR5 allosteric antagonist and the mGluR2/3 orthosteric agonist in rodents. FTIDC reduced maternal separationinduced ultrasonic vocalization and stress-induced hyperthermia without affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 39 publications
1
42
1
Order By: Relevance
“…In the present study, the doses of FTIDC were correlated with receptor occupancy in the brain, and a dose of 30 mg/kg almost fully inhibited (S)-3,5-DHPGinduced face-washing behavior. In contrast, the doses of FTIDC in the present study neither decreased spontaneous locomotor activity nor impaired rotorod performance (20). These results suggested that motor deficit was not elicited in mice at least at doses of FTIDC that significantly occupied mGluR1 in the brain and antagonized S-(3,5)-DHPG-induced face washing behavior.…”
contrasting
confidence: 46%
“…In the present study, the doses of FTIDC were correlated with receptor occupancy in the brain, and a dose of 30 mg/kg almost fully inhibited (S)-3,5-DHPGinduced face-washing behavior. In contrast, the doses of FTIDC in the present study neither decreased spontaneous locomotor activity nor impaired rotorod performance (20). These results suggested that motor deficit was not elicited in mice at least at doses of FTIDC that significantly occupied mGluR1 in the brain and antagonized S-(3,5)-DHPG-induced face washing behavior.…”
contrasting
confidence: 46%
“…In contrast, mGlu1 receptor antagonists neither induced catalepsy nor impaired rotarod performance [58,59], suggesting that mGlu1 receptor antagonists may not cause motor dysfunction, unlike the actions of typical antipsychotics. This atypical activity of mGlu1 receptor antagonists is further supported by c-fos induction, in that CFTI induces c-fos in the medial prefrontal cortex and nucleus accumbens, but not in the dorsolateral striatum, which is in line with the results using clozapine [58].…”
Section: Mglu1 Receptor Antagonistsmentioning
confidence: 94%
“…Of note, these mGlu1 receptor antagonists reduced maximal responses of L-glutamate [57,58], suggesting that both compounds acted as noncompetitive antagonists for the mGlu1 receptor. Thus, FITDC antagonized methamphetamine-induced locomotor hyperactivity and methamphetamine-disrupted PPI [59].…”
Section: Mglu1 Receptor Antagonistsmentioning
confidence: 99%
“…As reported here, these findings are similar to those seen when mice are pretreated with the prototypical mGlu5 antagonist MPEP (30 mg/kg). MPEP has been shown previously to reduce spontaneous nocifensive behaviors in the formalin test by several groups, with minimal effective doses in mice ranging from 10 mg/kg (Varty et al, 2005) to 30 mg/kg (Satow et al, 2008). We chose to make our comparison between fenobam and MPEP at a dose of 30 mg/kg because MPEP has been shown to be effective at 30 mg/kg in reducing formalin-induced nocifensive behaviors by multiple groups.…”
Section: Discussionmentioning
confidence: 99%